2022
DOI: 10.5194/essd-2022-346
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GRiMeDB: The global river database of methane concentrations and fluxes

Abstract: Abstract. Despite their small spatial extent, fluvial ecosystems play a significant role in processing and transporting carbon in aquatic networks, which results in substantial emission of methane (CH4) to the atmosphere. For this reason, considerable effort has been put into identifying patterns and drivers of CH4 concentrations in streams and rivers and estimating fluxes to the atmosphere across broad spatial scales. Yet progress toward these ends has been slow because of pronounced spatial and temporal vari… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
(37 reference statements)
0
17
0
Order By: Relevance
“…As has been reported elsewhere (Melton et al, 2013), much of the differences in bottom‐up estimates (and inverse estimates informed by priors from bottom‐up models) stem from how CH 4 emitting regions and wetland extent are identified (e.g., Melton et al, 2013; Zhang et al, 2017). As with most models, our accounting of CH 4 was terrestrially focused and did not provide estimates for rivers (see Stanley et al, 2022), open water lakes and ponds.…”
Section: Discussionmentioning
confidence: 99%
“…As has been reported elsewhere (Melton et al, 2013), much of the differences in bottom‐up estimates (and inverse estimates informed by priors from bottom‐up models) stem from how CH 4 emitting regions and wetland extent are identified (e.g., Melton et al, 2013; Zhang et al, 2017). As with most models, our accounting of CH 4 was terrestrially focused and did not provide estimates for rivers (see Stanley et al, 2022), open water lakes and ponds.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Holgerson and Raymond (2016) have suggested that small ponds, in addition to wetlands, can be a strong CH 4 source. Recent studies of freshwater CH 4 emissions are likely to progressively fill the gaps in the budget (e.g., Johnson et al., 2022; Rosentreter et al., 2021; Stanley et al., 2022). Many observations have also detected substantial CH 4 emissions from tree stems (e.g., Barba et al., 2019), but those emissions are not explicitly accounted for in most biogeochemical models.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, these water samples are collected over a short period of time, often referred to as “grab” sampling (Turnbull et al 2017), which can usually only be considered to be representative for the period of sample collection. This is a concern because other studies have shown high temporal variability in aquatic CH 4 concentration (Podgrajsek et al 2014; Sieczko et al 2020; Stanley et al 2023) and because we have very little information on the temporal variability of 14 C in aquatic CH 4 . Moreover, the propensity to undertake sample collection during convenient, daylight hours, can lead to significant bias, as illustrated by Sieczko et al (2020) who found that aquatic CH 4 emissions were 2.4 times greater during the day compared to night.…”
Section: Introductionmentioning
confidence: 94%